Water Use Efficiency in Relation to Crop Production in Arid and Semi-arid Regions - Joshi, N L; Singh, D V (Annals of Arid Zone, 2016)
The major focus of present day agriculture has to be on increasing the efficiency of water use to achieve sustained production from finite water resources. Water use efficiency , (WUE) as assessed by various disciplines has been explained, but is discussed mainly from agronomic point of view. Various empirical models on water use developed to explain the relationship of total dry matter production or marketable yield with evapotranspiration and transpiration have been reviewed. The importance of increasing WUE by manipulation of management practices such as fertilizers, plant population and row width, weed control, rain-water harvesting and conservation, tillage, irrigation methods, and improving plant characteristics has been, emphasized. The role of mulches, antitranspirants and reflectants in reducing evapotranspiration to achieve higher WUE has also been evaluated. Management factors influencing crop water use have been assessed from the point of view of constraints and practicability in the field. The upper limit of WUE that 'should be targeted for optimum utilization of resources has been highlighted.